On conditions for the discreteness of the spectrum of a semiinfinite Jacobi matrix with zero diagonal - Masmaliev, G. M.; Khanmamedov, A. Kh. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We establish sufficient conditions for the discreteness of the spectrum of a second-order self-adjoint difference operator generated by a semiinfinite Jacobi matrix with zero principal diagonal.